Assessing the impact of recycled water quality and clogging on infiltration rates at a pioneering Soil Aquifer Treatment (SAT) site in Alice Springs, Northern Territory (NT), Australia - Barry, Karen E.; Vanderzalm, Joanne L.; Miotlinski, Konrad [UNESP]; Dillon, Peter J. (MDPI, 2017)
Infiltration techniques for managed aquifer recharge (MAR), such as soil aquifer treatment (SAT) can facilitate low-cost water recycling and supplement groundwater resources. However there are still challenges in sustaining adequate infiltration rates in the presence of lower permeability sediments, especially when wastewater containing suspended solids and nutrients is used to recharge the aquifer. To gain a better insight into reductions in infiltration rates during MAR, a field investigation was carried out via soil aquifer treatment (SAT) using recharge basins located within a mixture of fine and coarse grained riverine deposits in Alice Springs, Northern Territory, Australia. A total of 2.6 Mm3 was delivered via five SAT basins over six years; this evaluation focused on three years of operation (2011-2014), recharging 1.5 Mm3 treated wastewater via an expanded recharge area of approximately 38,400 m2. Average infiltration rates per basin varied from 0.1 to 1 m/day due to heterogeneous soil characteristics and variability in recharge water quality. A treatment upgrade to include sand filtration and UV disinfection (in 2013) prior to recharge improved the average infiltration rate per basin by 40% to 100%.
Keywords: Clogging; Infiltration rates; Managed aquifer recharge; Soil aquifer treatment